The genre of the business meeting: a corpus-based study - Handford, Michael J.A. (2007)
The present study analyses a corpus of audio recordings of authentic business meetings. The recordings were made in a variety of companies in the UK, and also in Eire, Germany and Japan. The companies which provided the data vary considerably in terms of area of business and size. The meetings themselves differ in terms of number of speakers, the relationships of the speakers, and the purposes and topics discussed; throughout the thesis the influence of these factors on communication is discussed.